Managing crisis communication via social media - Anja Špoljarić (Naše gospodarstvo / Our Economy, 2021)
Social media is becoming omnipresent in everyone's daily life, which is changing the way consumers think, act and buy. Organizations are aware of the possibilities that may occur from developing social media communication strategies, but oftentimes forget to predict and block negative consequences. Information spreadability and bad communication practices are the perfect trigger of a social media crisis, which is why it is crucial for organizations to know what kind of communication, both internal and external, they need to implement. To explore consumers' opinions on social media crisis communication, an online survey was conducted. 125 participants gave their insight into their expectations of the types and tone of social media messages organizations should communicate during a time of crisis. These findings could be used as a guideline for crisis communication planning, considering they examine what types of messages consumers prefer, and which medium of communication they prefer. Even though it is recognized that crisis situations can have a huge impact on an organization's wellbeing, consumers' perspective on crisis communication still has not been researched thoroughly.
Keywords: M31; M39; 330; public relations; crisis situation; social media; crisis communication; consumer perspective on crisis communication